151k views
2 votes
How to solve -18=6y+6(1+3y)

User Kumetix
by
4.4k points

2 Answers

2 votes

Answer:

y=-1

Explanation:

-18=6y+6(1+3y)

1. distribute the parentheses

-18=6y+6+18y

subtract the six from the -18

the six canceling each other out

-24=6y+18y

Add the variables

-24=24y

divide by 24

Y= -1

User Haney
by
5.4k points
4 votes

Answer:-1

Explanation:

I rewrote it so it looks like this:

6y+6(1+3y)=-18

6y+6(1)+6(3y)=-18

6y+6+18y=-18

24y+6=-18

-6 -6

24y=-24

24 24

y=-1

User Ripa Saha
by
4.7k points